2013
DOI: 10.1155/2013/360239
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bovine Serum Albumin Solubility in Aqueous Solutions by Intrinsic Viscosity Measurements

Abstract: The behavior of bovine serum albumin (BSA) in water is scarcely studied, and the thermodynamic properties arising from the experimental measurements have not been reported. Intrinsic viscosity measurements are very useful in assessing the interaction between the solute and solvent. This work discussed in a simple determination of the enthalpy of BSA in aqueous solution when the concentration ranges from 0.2 to 36.71% wt. and the temperature from 35 to 40 ∘ C. The relationship between the concentration and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In actual models the binding mechanism was also found to be dependent on protein size, polymer flexibility, and ratio between them. [3,[7][8][9][10][11] BSA is a relatively large globular protein, with wellknown structure and physicochemical properties, which possess nonhomogeneous charge distributions. BSA has also high water solubility owing to the large number of ionizable amino acids.…”
Section: Nanoparticles Tracking Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In actual models the binding mechanism was also found to be dependent on protein size, polymer flexibility, and ratio between them. [3,[7][8][9][10][11] BSA is a relatively large globular protein, with wellknown structure and physicochemical properties, which possess nonhomogeneous charge distributions. BSA has also high water solubility owing to the large number of ionizable amino acids.…”
Section: Nanoparticles Tracking Analysismentioning
confidence: 99%
“…[4] Studying the ability and behavior of assembling between a protein and a synthetic polymer is important for understanding the nature of interacting and as well for the development of new types of biohybrid materials. [5][6][7][8] If we take into consideration the possible interactions for bringing together proteins and polymers, as for example electrostatic and van der Waals forces, or covalent conjugation, as well as possible combinations of them, also, the impressive number of proteins and polymers available, their assembly became a versatile method to have novel biohybrid materials. In principle, a number of non-covalent forces contribute to complex formation between polymers and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2D) and 34.2 (data not shown), indicating a size slightly smaller than bovine serum albumin, MW 66.5 kDa. 16 Elution profiles showed that the particles are monodisperse ( Figure 2D). …”
Section: Teg Particles Have a Consistent Core Diametermentioning
confidence: 99%
“…where v H is hydrodynamic volume (cm 3 ) from measured R H , and M is the molecular weight (Da or g mol −1 ) (Masuelli [31]). The magnitude of v can be determined by density measurements varying the biopolymer-water ratio as…”
Section: The Intrinsic Viscosity Denoted By [η]mentioning
confidence: 99%